2021
DOI: 10.1016/j.amsu.2021.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma and urine NGAL with acute kidney injury after elective colorectal surgery: A cohort study

Abstract: Background Acute kidney injury (AKI) is common in surgical patients. We aimed to investigate the validity of plasma and urine neutrophil gelatinase-associated lipocalin (NGAL) in the detection of AKI and prediction of outcomes in patients undergoing major colorectal surgery. Materials and methods This was a pre-specified post-hoc analysis of a randomized controlled trial comparing oesophageal doppler and Lithium dilution cardiac output monitoring in high risk patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In the current study, 10.3% of the patients developed AKI postoperatively (80% of them stage 1, 18% stage 2, and 2% stage 3). These ndings are consistent with Lumlertgul et al who studied 89 patients undergoing CRC surgery and observed AKI in 13.5% of them (75% AKI stage 1, 17% stage 2, and 1 patient stage 3) [10]. Also, a meta-analysis by O'Connor et al on 19 articles describing AKI outcomes in 82,514 patients post major abdominal surgery including CRC surgery, found that pooled incidence of AKI was 13.4% [11].…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, 10.3% of the patients developed AKI postoperatively (80% of them stage 1, 18% stage 2, and 2% stage 3). These ndings are consistent with Lumlertgul et al who studied 89 patients undergoing CRC surgery and observed AKI in 13.5% of them (75% AKI stage 1, 17% stage 2, and 1 patient stage 3) [10]. Also, a meta-analysis by O'Connor et al on 19 articles describing AKI outcomes in 82,514 patients post major abdominal surgery including CRC surgery, found that pooled incidence of AKI was 13.4% [11].…”
Section: Discussionsupporting
confidence: 86%
“…Researches have indicated several biomarkers for predicting perioperative complications, including B-type natriuretic peptide (BNP) [ 7 ], neutrophil gelatinase-associated lipocalin (NGAL) [ 8 ] and S100B protein [ 9 ]. These predictive biomarkers reflect heterogeneity in individual responses to surgery and could not be dynamically assessed perioperatively.…”
Section: Introductionmentioning
confidence: 99%
“…However, as damage markers of organs, one biomarker only show predictive value in one specific organ or system. For example, as a marker of tubular damage, NGAL has been demonstrated closely associated with acute kidney injury (AKI) after cardiac and colorectal surgery [ 8 , 10 ]. Therefore, there is a pressing need for new biomarkers to predict the overall risk of aging people during perioperative period.…”
Section: Introductionmentioning
confidence: 99%